Electrolytic Disinfection of Irrigation Water for Intensive Crop Production in Greenhouses as Demonstrated on Tomatoes (Solanum lycopersicum Mill) (2022)
Shortage of water availability and awareness of the need for sustainable resource management have generated a significant increase in the use of recycled water for irrigation and processing of crops and harvest products, respectively. As a result, irrigation systems face the challenge of neutralizing plant pathogens to reduce the risk of their dispersal and the subsequent occurrence of diseases with potentially high economic impacts. We evaluated the efficacy of an innovative electrolytic disinfection system based on potassium hypochlorite (KCLO) to inactivate major pathogens in hydroponically grown tomatoes: Fusarium oxysporum (Synder and Hans), Rizocthonia solani (Kühn), Tobacco mosaic virus (TMV) and Pepino mosaic virus (PepMV). The electrolytically derived disinfectant was prepared on-site and added to the recirculating fertigation solution once a week for 60 min in an automated manner using sensor technology at a dosage of 0.5 mg of free chlorine/L (fertigation solution at pH 6.0 ± 0.3 and ORP 780 ± 31 mV). Tomato fruit yield and pathogen dispersal were determined for 16 weeks. At the applied dosage, the disinfectant has been shown to inhibit the spread of plant pathogenic fungi and, remarkably, plant viruses in recirculating fertigation solutions. Phytotoxic effects did not occur.